Samantha Beall COVID-19 Home Garden Narrative - Beall, Samantha::::::::: (2021)
Photographs of seed packs and potted plants grown by Beall and fiancé during the COVID-19 Shelter-in-Place order. Beall expresses motivation to start a home herb and vegetable garden because of the inconvenience and safety concerns of shopping in grocery stores.